2017
DOI: 10.1002/2211-5463.12332
|View full text |Cite
|
Sign up to set email alerts
|

The SWEET gene family in Hevea brasiliensis – its evolution and expression compared with four other plant species

Abstract: SWEET proteins play an indispensable role as a sugar efflux transporter in plant development and stress responses. The SWEET genes have previously been characterized in several plants. Here, we present a comprehensive analysis of this gene family in the rubber tree, Hevea brasiliensis . There are 36 members of the SWEET gene family in this species, making it one of the largest families in plant genomes sequenced so far. Structure and phylogeny analyses of these gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 37 publications
(64 reference statements)
5
16
0
Order By: Relevance
“…In previous reports, the SWEET gene family has been characterized in various plant species, such as Arabidopsis [1], rice [30], sweet orange [31], soybean [11], tomato [32], potato [33], sorghum [34], cucumber [5,35], rubber tree ( Hevea brasiliensis ) [36], pineapple ( Ananas comosus ) [37], apple [38], tea plant [39], Chinese cabbage ( Brassica rapa ) [40,41], wheat [13,42], and cabbage ( B. oleracea ) [43]. However, the SWEET gene family in Medicago truncatula is still poorly understood, and the biological functions of MtSWEETs remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In previous reports, the SWEET gene family has been characterized in various plant species, such as Arabidopsis [1], rice [30], sweet orange [31], soybean [11], tomato [32], potato [33], sorghum [34], cucumber [5,35], rubber tree ( Hevea brasiliensis ) [36], pineapple ( Ananas comosus ) [37], apple [38], tea plant [39], Chinese cabbage ( Brassica rapa ) [40,41], wheat [13,42], and cabbage ( B. oleracea ) [43]. However, the SWEET gene family in Medicago truncatula is still poorly understood, and the biological functions of MtSWEETs remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In general, a typical angiosperm genome contains 15 to 25 SWEET genes, e.g., 17 are encoded in Arabidopsis and 21 in rice. SWEET gene duplication occurs during evolution in numerous plant species, such as Eucalyptus (47 genes) [14], soybean (52) [21], wheat (108) [22], cabbage (30) [23], cultivated cotton (55) [24], and rubber tree (36) [25], contrary to only one single gene encoded by human and Drosophila genomes [16,26]. The four-clade classified SWEET proteins play very important roles in diverse physiological and pathophysiological processes (recent reviews in [14,27,28]).…”
Section: Introductionmentioning
confidence: 99%
“…LcMCII-1 is positively involved in the regulation of rudimentary leaf senescence in litchi (Wang et al 2017). In the rubber tree (Hevea brasiliensis), the results derived from RNA-seq analyses demonstrated that SWEET2, 16, and 17 might represent the main direction of evolution of the SWEET genes in plants (Sui et al 2017).…”
Section: Rna-seq and Single-cell Rna Sequencing In Woody Plantsmentioning
confidence: 99%
“…RNA-Seq technology has been used to investigate the cork developmental in hybrid poplar (Populus tremula 9 Populus alba) and 455 candidate genes that are responsible for the biosynthesis of poplar suberin have been identified (Rains et al 2018). RNA-seq analyses have identified the involvement of PtSWEET16b and PtSWEET16d genes in xylem development of P. trichocarpa (Sui et al 2017). RNA-seq analyses have also identified a large number of regulators that are was related to DNA and histone methylation (Yakovlev et al 2016).…”
Section: Poplarmentioning
confidence: 99%